The study of diseases of sturgeon fish farms Zharkent region (Eurasian Journal of Ecology, 2016)
Literature data and the results of studies on various fish diseases in general and in particular sturgeon. Diseases are not insured neither fish farm. When you create a certain favorable conditions the disease can occur in any economy. It may begin during any development cycle of fish (from caviar to merchantability). It is therefore important to know the basic questions ichthyopathology, diagnosis, prevention and treatment of diseases of sturgeons.
Keywords: sturgeon; aquaculture; fish diseases; infectious diseases; viral diseases; parasitic diseases; nutrition-related diseases.